Răspuns :
25 + ( 99 - 9 : 9 - 4 × 9 ) =
25 + ( 99 - 1 - 36 ) =
25 + 98 - 36 =
123 - 36 = 87
( 6 × 3 ) + ( 54 - 3 × 2 × 8 ) =
18 + ( 54 - 48 ) =
18 + 6 = 24
3 × ( 20 : 10 × 5 ) + ( 63 : 9 - 7 ) =
3 × ( 2 × 5 ) + ( 7 - 7 ) =
3 × 10 + 0 =
30 + 0 = 30
Sᴀʟᴜᴛᴀʀᴇ!
[tex] 25 + ( 99 - 9 \div 9 - 4 \times 9) = \\ 25 + (99 - 1 - 36) = \\ 25 +( 98 - 36) = \\ 25 + 62 = \\ 87 \\ \\ (6 \times 3) + (54 - 3 \times 2 \times 8) = \\ 18 + (54 - 6 \times 8) = \\ 18 + (54 - 48) = \\ 18 + 6 = \\ 24 \\ \\ 3 \times (20 \div 10 \times 5) + (63 \div 9 - 7) = \\ 3 \times (2 \times 5) + (7 - 7) = \\ 3 \times 10 + 0 = \\ 30 + 0 = \\ 30[/tex]
Succes!